Neuromodulation in new-onset refractory status epilepticus - Stavropoulos, Ioannis; Khaw, Jin Han; Valentin, Antonio (Frontiers in Neurology, 2023)
Background: New onset refractory status epilepticus (NORSE) and its subset febrile infection-related epilepsy syndrome (FIRES) are devastating clinical presentations with high rates of mortality and morbidity. The recently published consensus on the treatment of these conditions includes anaesthetics, antiseizure drugs, antivirals, antibiotics and immune therapies. Despite the internationally accepted treatment the outcome remains poor for a significant percentage of patients. Methods: We conducted a systematic review about the use of neuromodulation techniques in the treatment of the acute phase of NORSE/FIRES using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results: Our search strategy brought up 74 articles of which 15 met our inclusion criteria. A total of 20 patients were treated with neuromodulation. Thirteen cases represented FIRES and in 17 cases the NORSE remained cryptogenic. Ten had electroconvulsive therapy (ECT), 7 had vagal nervous stimulation (VNS) and 4 had deep brain stimulation (DBS) (1 patient had initially VNS and later DBS). Eight patients were female and 9 were children. In 17 out of 20 patients the status epilepticus was resolved after neuromodulation while 3 patients died. Conclusion: NORSE can have a catastrophic course, and the first treatment goal should be the fastest possible termination of status epilepticus. The data presented are limited by the small number of published cases, and the variability of neuromodulation protocols used. However, they show some potential clinical benefits of early neuromodulation therapy suggesting that these techniques could be considered at earlier stages within the course of FIRES/NORSE.